Assessment of biomechanical properties in pulmonary arterial hypertension: a computational fluid dynamics study of the extensive pulmonary arterial tree - Jian Shi; Jianwen Liang; Jieting Wang; Hui Wang; Zhenyu Wang; Xiaocong Zhang; Guifu Wu; Shuai Tian; Wenbin Wei (BMC Pulmonary Medicine)
Abstract Biomechanical forces play a central role in the pathophysiology of pulmonary arterial hypertension (PAH). Due to the numerous branches and complex structure of the pulmonary arteries, three-dimensional reconstruction poses significant challenges, resulting in a lack of comprehensive hemodynamic studies encompassing the entire pulmonary arterial tree in PAH. This study employs computational fluid dynamics (CFD) to evaluate the biomechanical properties of the extensive pulmonary artery tree (segmented up to 6 th-generation branches) in PAH. Key hemodynamic parameters, including velocity, wall shear stress (WSS), time-averaged wall shear stress (TAWSS), oscillatory shear index (OSI), and relative residence time (RRT), were meticulously computed. Results revealed a significant decrease in outlet cross-sectional area (p < 0.0001) and a notable increase in outlet velocity compared to the inlet (p < 0.05) and main body (p < 0.001). WSS in the proximal pulmonary artery was consistently lower than in the distal pulmonary artery for all subjects, with low TAWSS observed in proximal arteries. Helical flow patterns were predominantly seen in proximal pulmonary arteries of PAH subjects. Additionally, high OSI and RRT values were noted within the proximal arteries. This study provides a comprehensive evaluation of hemodynamic parameters in PAH, identifying velocity, WSS, OSI, and RRT as valuable markers of its distinct biomechanical characteristics. These findings shed light on the complex interplay of biomechanical forces in PAH.